Analysis and calculation of the steel tank according to Eurocode and API 650 - Bešević Miroslav; Pavić Milica (Zbornik Radova Građevinskog Fakulteta, 2022)
This paper presents a calculation of a steel vertical water tank, with a total height of 19,2 m and a diameter of 8,59 m. The construction of this tank was modelled using the ABAQUS software package, whereby a realistic picture of the stress notations in the walls of the tank was obtained. The structural load analysis was performed based on European and American standards, as well as comparison of the obtained results.